Draft Genome Sequences of 12 Isolates from 3 Fusarium Species Recovered from Moldy Peanuts - Gebru, Solomon T. (Microbiol Resour Announc, 2019)
In this report, we announce the sequences of six genomes of Fusarium proliferatum (isolates MOD1-FUNGI8, -12, -13, -14, -15, and -19), four genomes of Fusarium oxysporum (MOD1-FUNGI9, -10, -11, and -16), and two genomes of the Fusarium incarnatum-Fusarium equiseti species complex (MOD1-FUNGI17 and MOD1-FUNGI18) isolated from moldy peanuts from the Washington, DC, area.